2018
DOI: 10.1155/2018/7647980
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Thymus in Short-Term Calorie-Restricted Mice Using RNA-seq

Abstract: Calorie restriction (CR), which is a factor that expands lifespan and an important player in immune response, is an effective protective method against cancer development. Thymus, which plays a critical role in the development of the immune system, reacts to nutrition deficiency quickly. RNA-seq-based transcriptome sequencing was performed to thymus tissues of MMTV-TGF-α mice subjected to ad libitum (AL), chronic calorie restriction (CCR), and intermittent calorie restriction (ICR) diets in this study. Three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Thymus transcriptome analysis in short-term CR mice showed that CR altered catalytic activity and metabolic processes (Omeroglu Ulu et al, 2018). Short-term CR also altered the expression of leptin, ghrelin, Igf1, and adiponectin, some of which were reported to be associated with age-related thymic involution (Omeroglu Ulu et al, 2018).…”
Section: Metabolic Regulation Of Thymic Involutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymus transcriptome analysis in short-term CR mice showed that CR altered catalytic activity and metabolic processes (Omeroglu Ulu et al, 2018). Short-term CR also altered the expression of leptin, ghrelin, Igf1, and adiponectin, some of which were reported to be associated with age-related thymic involution (Omeroglu Ulu et al, 2018).…”
Section: Metabolic Regulation Of Thymic Involutionmentioning
confidence: 99%
“…Another study conducted on nonhuman primates obtained similar results; the authors showed that long‐term CR effectively improves naïve T‐cell production and preserves T‐cell receptor repertoire diversity (Messaoudi et al, 2006). Thymus transcriptome analysis in short‐term CR mice showed that CR altered catalytic activity and metabolic processes (Omeroglu Ulu et al, 2018). Short‐term CR also altered the expression of leptin, ghrelin, Igf1, and adiponectin, some of which were reported to be associated with age‐related thymic involution (Omeroglu Ulu et al, 2018).…”
Section: Age‐related Thymic Involution Mechanismsmentioning
confidence: 99%
“…CR decreases the expression of pro-EMT and proadipogenic regulators, such as fibroblast-specific protein-1, FoxC2, PPARγ, and FABP4, in the thymus of aged mice (91). The increase in the expression of molecules related to the prevention of thymic involution, including ghrelin, leptin, and Igf1, in the thymus of short-term calorie-restricted mice has also been reported (91,92). A recent study on healthy humans has reported that a 14% reduction in calorie intake enhances thymic mass and function (93).…”
Section: Age-related Chronic Thymic Involutionmentioning
confidence: 83%